Marketing higher education : understanding how to build and promote the university brand - Koku, Paul Sergius, 1955- (Routledge, Taylor & Francis Group, 2023)
"This book provides a comprehensive and accessible guide to marketing Higher Education institutions, discussing both how universities are service providers and how education is a service, both of which need to be defined and marketed together. Unlike the current offering available on the subject, this book provides a uniquely applied approach, linking the theory of marketing practice and how it relates to the Higher Education sector through real life case studies and examples. Each topic is covered in depth, including marketing segmentation, pricing, location, brand management, internationalization and expansion. Overarchingly, the book considers how to develop and promote the University as a product and as a brand. Two case studies from real life universities in a broad range of locations are provided at the end of each chapter, alongside questions to aid understanding and application. Holistic and practical, Marketing Higher Education is an ideal guide for academics and students studying services marketing, Higher Education management and leadership, and marketing in the public sector. It will also be an invaluable resource for professionals working in Higher Education administration looking to develop their skills and understanding of marketing and brand building"- Resumé vydavatel
Keywords: vysoké školy; marketing; marketingový management; řízení značky; universities and colleges; marketing management; brand management; branding (marketing); příručky; případové studie; handbooks and manuals; case studies